Filling the dead‐time gap in zero echo time MRI: Principles compared. Issue 4 (30th August 2017) - Froidevaux, Romain; Weiger, Markus; Brunner, David O.; Dietrich, Benjamin E.; Wilm, Bertram J.; Pruessmann, Klaas P.
Abstract : Purpose: MRI of tissues with short coherence lifetimes T2 or T 2 * can be performed efficiently using zero echo time (ZTE) techniques such as algebraic ZTE, pointwise encoding time reduction with radial acquisition (PETRA), and water‐ and fat‐suppressed proton projection MRI (WASPI). They share the principal challenge of recovering data in central k‐space missed due to an initial radiofrequency dead time. The purpose of this study was to compare the three techniques directly, with a particular focus on their behavior in the presence of ultra–short‐lived spins. Methods: The most direct comparison was enabled by aligning acquisition and reconstruction strategies of the three techniques. Image quality and short‐ T 2 * performance were investigated using point spread functions, 3D simulations, and imaging of phantom and bone samples with short (<1 ms) and ultra‐short (<100 μs) T 2 * . Results: Algebraic ZTE offers favorable properties but is limited to k‐space gaps up to approximately three Nyquist dwells. At larger gaps, PETRA enables robust imaging with little compromise in image quality, whereas WASPI may be prone to artifacts from ultra‐short T 2 * species. Conclusion: For small k‐space gaps (<4 dwells) and T 2 * much larger than the dead time, all techniques enable artifact‐free short‐ T 2 * MRI. However, if these requirements are not fulfilled careful consideration is needed and PETRA will generally achieve better image quality. Magn Reson Med 79:2036–2045, 2018. © 2017 International Society for Magnetic Resonance in Medicine.